Enhancement of β‐Globin Gene Expression in Thalassemic IVS2‐654 Induced Pluripotent Stem Cell‐Derived Erythroid Cells by Modified U7 snRNA. (18th February 2017) - Phanthong, Phetcharat; Borwornpinyo, Suparerk; Kitiyanant, Narisorn; Jearawiriyapaisarn, Natee; Nuntakarn, Lalana; Saetan, Jirawat; Nualkaew, Tiwaporn; Sa‐ngiamsuntorn, Khanit; Anurathapan, Usanarat; Dinnyes, Andras; Kitiyanant, Yindee; Hongeng, Suradej
Abstract: The therapeutic use of patient‐specific induced pluripotent stem cells (iPSCs) is emerging as a potential treatment of β‐thalassemia. Ideally, patient‐specific iPSCs would be genetically corrected by various approaches to treat β‐thalassemia including lentiviral gene transfer, lentivirus‐delivered shRNA, and gene editing. These corrected iPSCs would be subsequently differentiated into hematopoietic stem cells and transplanted back into the same patient. In this article, we present a proof of principle study for disease modeling and screening using iPSCs to test the potential use of the modified U7 small nuclear (sn) RNA to correct a splice defect in IVS2‐654 β‐thalassemia. In this case, the aberration results from a mutation in the human β‐globin intron 2 causing an aberrant splicing of β‐globin pre‐mRNA and preventing synthesis of functional β‐globin protein. The iPSCs (derived from mesenchymal stromal cells from a patient with IVS2‐654 β‐thalassemia/hemoglobin (Hb) E) were transduced with a lentivirus carrying a modified U7 snRNA targeting an IVS2‐654 β‐globin pre‐mRNA in order to restore the correct splicing. Erythroblasts differentiated from the transduced iPSCs expressed high level of correctly spliced β‐globin mRNA suggesting that the modified U7 snRNA was expressed and mediated splicing correction of IVS2‐654 β‐globin pre‐mRNA in these cells. Moreover, a less active apoptosis cascade process was observed in the corrected cells at transcription level. This study demonstrated the potential use of a genetically modified U7 snRNA with patient‐specific iPSCs for the partial restoration of the aberrant splicing process of β‐thalassemia. Stem Cells Translational Medicine 2017;6:1059–1069